Open market share repurchase programs and corporate governance: Company performance - CATON, Gary (Institutional Knowledge at Singapore Management University, 2015)
Payout policies based on share repurchase programs provide greater flexibility than do those based on cash dividends. We develop and test an empirical model in which strongly-governed companies outperform weakly-governed companies after announcing share repurchase programs. Our findings include positive associations between strong governance and both post-announcement adjusted operating performance and abnormal stock returns. The results are robust to sample selection bias, different sample criteria, governance measurement, and various control variables. In addition, governance strength is associated with larger post-announcement changes in CEO incentive compensation and merger and acquisition activity, both of which we argue are consistent with strongly-governed companies using the financial flexibility derived from choosing share repurchases over cash dividends to drive better performance. Consistent with current literature on attenuation of former anomalies, the associations we find between governance and post-announcement performance tend to disappear in the latter half of our sample period.